The Role of Part-Time Learning in Developing Personal Leadership - Rusli, Al Juan (2009)
There are numerous books, journals, and other literature available on the topic of leadership but the relationship between leadership and part-time learning has yet to be explored in depth and therefore provides an opportunity for further study. Developing leadership is not just based on the axis of the ‘nature versus nurture’ dichotomy, but it can also be cultivated through direct experience. The demands, pacing, and characteristics of part-time learning introduce an avenue for the improvement of personal qualities. This dissertation analyzes the role of part-time learning in developing personal leadership. The findings of this study indicate that personal qualities including personal leadership qualities) were improved as a result of going through a process of learning. Keywords: Part-time learning, goal-setting, personal leadership.